Development of the Mealtime Emotions Measure for adolescents (MEM-A): Gender differences in emotional responses to family mealtimes and eating psychopathology. (1st February 2015) - White, Hannah J.; Haycraft, Emma; Wallis, Deborah J.; Arcelus, Jon; Leung, Newman; Meyer, Caroline
Highlights: The Mealtime Emotions Measure for adolescents (MEM-A) was developed and validated. MEM-A subscales tap Anxiety-related, Anger-related and Positive mealtime emotions. Girls reported experiencing more Anxiety-related mealtime emotions than boys. Findings suggest some mealtime emotions are associated with eating psychopathology. Highlights value of positive mealtime environments to help reduce disordered eating. Abstract: This study aimed to examine the factor structure of the Mealtime Emotions Measure for adolescents (MEM-A), a novel measure of emotional responses experienced during family mealtimes. Additionally, it examined gender differences in mealtime emotions and also the relationships between mealtime emotions and levels of eating psychopathology, when controlling for anxiety or depression. Adolescent participants (N = 527; 282 girls, 245 boys) with a mean age of 15.9 years completed the new mealtime measure for adolescents (MEM-A), in addition to questions about family mealtime atmosphere, and measures assessing symptoms of anxiety, depression, and eating psychopathology. Factor analysis produced a three factor solution for the MEM-A with two subscales relating to different types of negative mealtime emotions ( Anxiety-related mealtime emotions and Anger-related mealtime emotions ) and one subscale relating to Positive mealtime emotions . Generally, girls reported experiencing more Anxiety-related mealtime emotions compared to boys. Having conducted separate analyses controlling for levels of either anxiety or depression, there were several significant associations for both girls and boys between mealtime emotions, particularly Anxiety-related emotions, and eating psychopathology. The findings suggest that some mealtime emotions are associated with increased eating psychopathology. Replication and detailed examination of these emotional responses is required.